Effect of the rheological properties of carbon nanotube dispersions on the processing and properties of transparent conductive electrodes - Maillaud, Laurent (Langmuir : the ACS journal of surfaces and colloids, 2015)
Transparent conductive films are made from aqueous surfactant stabilized dispersions of carbon nanotubes using an up-scalable rod coating method. The processability of the films is governed by the amount of surfactant which is shown to alter strongly the wetting and viscosity of the ink. The increase of viscosity results from surfactant mediated attractive interactions between the carbon nanotubes. Links between the formulation, ink rheological properties, and electro-optical properties of the films are determined. The provided guidelines are generalized and used to fabricate optimized electrodes using conductive polymers and carbon nanotubes. In these electrodes, the carbon nanotubes act as highly efficient viscosifiers that allow the optimized ink to be homogeneously spread using the rod coating method. From a general point of view and in contrast to previous studies, the CNTs are optimally used in the present approach as conductive additives for viscosity enhancements of electronic inks